Land Use and its Impact on Agricultural Productivity in Mutara Sub-County Mitooma District. - Tusingwire, Pamellah (Kabale University, 2024)
The study explored the relationship between land use and agricultural productivity in Mutara Sub-county, Mitooma District. It aimed to identify the factors influencing farmers' land management decisions, analyze the impact of current land use practices on agricultural productivity, and recommend strategies to improve sustainable land use practices and enhance productivity in the region. The study employed a cross-sectional survey design, utilizing both qualitative and quantitative approaches. A sample of 99 respondents, determined using Slovin's formula, was selected, including household heads, the Sub-county Community Development Officer, the Agricultural Officer, LCIII, and Parish Chief from one of Mutara Sub-county's parishes. Purposive and simple random sampling techniques were used, and data was collected using questionnaires and interview guides. Descriptive analysis was performed to determine the proportions and frequencies of the variables. The findings indicated that the cost of inputs such as fertilizers, pesticides, seeds, labor, and machinery significantly influences farmers' decisions on crop selection and land management, with 57% strongly agreeing, 49% agreeing, and 4% disagreeing. The study also found that sustainable land management practices, like crop rotation, cover cropping, and reduced tillage, can enhance soil structure, fertility, and water retention. This was supported by 62% strongly agreeing, 28% agreeing, 27% disagreeing, and 11% strongly disagreeing. Improving soil fertility was highlighted as crucial for increasing agricultural productivity. The study suggested that farmers should be encouraged to use organic fertilizers, such as compost or manure, and recommended establishing community composting programs to recycle organic waste into valuable fertilizers. This was supported by 52% strongly agreeing, 43% agreeing, and 5% disagreeing. The study concluded that collaborative farming initiatives within communities positively impact productivity by pooling resources for better input access and shared knowledge on best practices. It also emphasized that traditional farming methods and cultural beliefs significantly influence land management decisions, with some farmers reluctant to adopt new technologies due to adherence to generational practices. The study recommended conducting regular assessments of current land use practices to evaluate their effectiveness in boosting agricultural productivity, including analyzing crop yields, soil health, and biodiversity levels.